2017
DOI: 10.1007/s12639-017-0937-z
|View full text |Cite
|
Sign up to set email alerts
|

Studies on theileriosis in goats from Karnataka, South India

Abstract: A study was conducted to determine the prevalence of theileriosis in goats from southern districts of Karnataka. Out of 47 goat blood samples examined by microscopy, 68.08% (32/47) were positive for spp. The parasitemia ranged from 1.0 to 1.8 and 0.1-0.9% in clinical and carrier animals respectively. Out of 325 ticks collected from goats, 92.6 (301) and 7.38 (24)% of the ticks were found to be and respectively. (90.15%) was found to be the predominant species followed by (6.7%), (1.84%), (0.61%) and (0.61%). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
1
1
1
Order By: Relevance
“…This is consistent with the presentation of tick-borne blood parasitic disease reported in other literature [ 2 ]. However, the significant increase of MCH in this study is inconsistent with the substantial decrease in MCH reported by Shruthi [ 20 ], which may be due to that the different infecting Theileria species. However, this needs to be investigated in subsequent studies.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the presentation of tick-borne blood parasitic disease reported in other literature [ 2 ]. However, the significant increase of MCH in this study is inconsistent with the substantial decrease in MCH reported by Shruthi [ 20 ], which may be due to that the different infecting Theileria species. However, this needs to be investigated in subsequent studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Theileria lestoguardi, T. uilenbergi, and T. luwenshuni are highly harmful species for small ruminants, while T. ovis and T. separate are low pathogenic species (Yin et al, 2007) [10] . Previous observations provide support for the clinical symptoms in this case (Shruthi et al, 2017) [8] . Anaemia was the cause of the dyspnea and tachycardia.…”
Section: Discussionsupporting
confidence: 82%
“…The presence of comma-and parachute-shaped piroplasms in the red blood cells (RBCs) in this goat case confirmed theileria infection, which was also described by Altay et al (2007) [3] . Pleomorphic piroplasms in red blood cells of Theileriaaffected goats, comprising rod, pear, dot, nail, comma, oval, parachute, round, and semi-comma shapes, were reported by Shruthi et al (2017) [8] in the Indian state of Karnataka. Microscopical analysis of stained blood smears can be used as a quick confirmatory diagnostic test for the start of curative treatment in animals affected by Theileriosis, even though it is less sensitive than molecular techniques like polymerase chain reaction (PCR) for the detection of low levels of parasitaemia in theileriosis affected animals (Rabeya Begam et al, 2019) [7] .…”
Section: Discussionmentioning
confidence: 80%